Study on spatial distribution of coral reefs in Nam Yet island by using GIS and remote sensing techniques - Tung, Nguyen Xuan; Cuong, Do Huy; Anh, Bui Thi Bao; Nhan, Nguyen Thi; Luan, Nguyen The; Hung, Pham Duc (Vietnam Journal of Marine Science and Technology, 2019)
Research and application of GIS and remote sensing techniques combined with field survey in coastal areas of Nam Yet island had been carried out to establish the distribution map of submarine habitats. Depth-invariant index was used to correct water column’s effects on spectral reflectance of each habitat. The results of satellite image classification showed that area with well-developed coral at great depths accounted for 12%, area with well-developed coral at small depths accounted for 9%, area with poorly-developed coral accounted for 13%, dead coral area accounted for 15% and area of sand, grit, pebbles and weathered coral accounted for 51%. The assessment after classification showed that the overall accuracy of the satellite image interpretation process was 94% and the kappa coefficient was 0.93.